2007
DOI: 10.1111/j.1750-3841.2007.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Yerba Mate Tea (Ilex paraguariensis): A Comprehensive Review on Chemistry, Health Implications, and Technological Considerations

Abstract: Yerba Mate tea, an infusion made from the leaves of the tree Ilex paraguariensis, is a widely consumed nonalcoholic beverage in South America which is gaining rapid introduction into the world market, either as tea itself or as ingredient in formulated foods or dietary supplements. The indigenous people have used it for centuries as a social and medicinal beverage. Yerba Mate has been shown to be hypocholesterolemic, hepatoprotective, central nervous system stimulant, diuretic, and to benefit the cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
558
1
38

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 666 publications
(608 citation statements)
references
References 104 publications
(144 reference statements)
11
558
1
38
Order By: Relevance
“…This showed the ability of Ku Ding tea to reduce the rat body weight and this effect was more evident in the male than in female rats. Ilex species has been suggested for obesity management (Heck and Mejia 2007) and Ku Ding tea has also been believed to have weight loss properties in China. Zheng (2003) reported that 20 days administration of total terpene (TT) of Ku Ding tea to nutritional obese SD rats resulted in reduction of body weight.…”
Section: Resultsmentioning
confidence: 99%
“…This showed the ability of Ku Ding tea to reduce the rat body weight and this effect was more evident in the male than in female rats. Ilex species has been suggested for obesity management (Heck and Mejia 2007) and Ku Ding tea has also been believed to have weight loss properties in China. Zheng (2003) reported that 20 days administration of total terpene (TT) of Ku Ding tea to nutritional obese SD rats resulted in reduction of body weight.…”
Section: Resultsmentioning
confidence: 99%
“…Benefícios para a saúde têm sido atribuídos à erva-mate, com ação hipocolesterolêmica, hepatoprotetora, estimulante do sistema nervoso central e antioxidante pela presença de metabólitos ativos. Dentre eles, apresentam-se em concentrações signifi cativas os polifenóis (ácidos clorogênicos), as xantinas (cafeína e teobromina), seguidos dos fl avonoides (quercetina, kaempferol e rutina), entre outros (HECK; MEJIA, 2007).…”
Section: Componentesunclassified
“…Na análise do material resinoso, a indicação da presença desse metabólito é decorrente do desenvolvimento de coloração azulada/violácea/roxa ou amarela (prolina e hidroxi-prolina) com o reativo de ninhidrina, confi rmada pela coloração violácea em placas de sílica gel, tanto para o extrato aquoso como para o hidroalcoólico, confi rmando o estudo de Cardozo Júnior et al (2007 a,b) em amostras de folhas de erva-mate A presença de saponinas confi rmadas na aná-lise são substâncias glicosídicas com a propriedade de, em soluções aquosas, provocarem a formação de espumas devido à redução da tensão superficial. Apresentam ação detergente e emulsifi cante e, na erva-mate, são responsáveis pelo índice de amargor e espuma do produto (SUERTEGARAY, 2002;GNOATTO, SCHENKEL;BASSANI, 2005;BRAVO, GOYA;LECUMBERRI, 2007;HECK;MEJIA, 2007). Essa capacidade deve-se à presença de propriedades emulsivas nas saponinas.…”
Section: Componentesunclassified
See 1 more Smart Citation
“…The extracts contain mainly polyphenols like chlorogenic acid, purine alkaloids (methylxanthines) such as caffeine and theobromine, flavonoids, a combination of vitamins, tannins and numerous triterpenic saponins derived from ursolic acid [5,7,14]. The polyphenolic compounds of major importance in mate refer to caffeoyl derivatives, mainly monocaffeoyl quinic isomers and dicaffeoyl quinic isomers [7], and their level exceeds even that found in green tea, a typical 'antioxidant' product present on the market.…”
Section: Introductionmentioning
confidence: 99%